2020
DOI: 10.1016/j.ejro.2020.100254
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism: Low dose contrast MSCT pulmonary angiography with modified test bolus technique

Abstract: Highlights Test bolus technique increase the diagnostic quality score of the scans performed. Provides better evaluation of the pulmonary arteries and its subsegmental branches. Increase the main pulmonary artery average density, decrease average density of the aorta and pulmonary veins. Increase the confidence and accuracy rate of diagnostic examinations. Volume of IV contrast decreased by 40 % than in bolus tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 17 publications
(22 reference statements)
1
5
5
Order By: Relevance
“…found no significant differences in pulmonary artery enhancement between both techniques. The results from this study are in contrast with Kamr et al 11 . who performed a large prospective study on 600 patients comparing both techniques.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…found no significant differences in pulmonary artery enhancement between both techniques. The results from this study are in contrast with Kamr et al 11 . who performed a large prospective study on 600 patients comparing both techniques.…”
Section: Discussioncontrasting
confidence: 97%
“…research demonstrated that bolus track resulted in a higher mean enhancement of the pulmonary artery. These findings differ from research by Kamr et al 11 . who recommend the test bolus protocol and Kerl et al 12 .…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations